219k views
0 votes
Helpppppppppppppppppppppppp

Helpppppppppppppppppppppppp-example-1

2 Answers

2 votes
Answer:
1 / 4x

Step-by-step explanation:
(4x^3) * (2x)^-4 = 4x^3 * 2^-4 * x^-4
= (4x^3) / (2^4 * x^4)
= (1/4) * (1/x)
= 1 / 4x

Hope this helps :)
User Szymon Wylezol
by
5.8k points
6 votes
First we rewrite the expression:
(4x ^ 3) * (2x) ^ - 4
Using properties of exponents we have:
(4x ^ 3) / (2x) ^ 4
Rewriting:
(4x ^ 3) / 16x ^ 4
(x ^ 3) / 4x ^ 4
(1) / (4x)
answer:
An equivalent expression is:
(1) / (4x)
option 1
User Randeep Singh
by
5.4k points